2020
DOI: 10.1016/j.heliyon.2020.e04350
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, development and characterization of a novel functional fruit snack based on fig (Ficus carica L.) coated with sugar-free chocolate

Abstract: The aim of the present investigation was to explore the possibility of developing a fruit snack formulation based on dried fig powder and chocolate-coated. Dried Fig ( Ficus carica L .) powder with a maximum particle size of 354 μm and the lowest compaction force was formulated as the core. Persian gum was prepared at the concentrations of 1.5, 2 and 2.5% and xanthan gum was prepared at the levels of 0.25, 0.39 and 0.54% as the middle layer to the coating of the core. Regarding rheologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Other studies have confirmed that a chocolate coating has a significant impact on sensorial characteristics, suggesting the potential for creating novel products that could achieve widespread consumer acceptance in the market. For example, Yeganehzad et al (2020) [9] reported that samples coated with chocolate scored higher (for appearance, flavor, texture, and total acceptance) than the core sample only. Likewise, Tassi et al (2019) [35] showed that roasted black soybeans with a chocolate coating were well accepted by young tasters, even if they did not have a habit of consuming soybeans.…”
Section: Sensory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have confirmed that a chocolate coating has a significant impact on sensorial characteristics, suggesting the potential for creating novel products that could achieve widespread consumer acceptance in the market. For example, Yeganehzad et al (2020) [9] reported that samples coated with chocolate scored higher (for appearance, flavor, texture, and total acceptance) than the core sample only. Likewise, Tassi et al (2019) [35] showed that roasted black soybeans with a chocolate coating were well accepted by young tasters, even if they did not have a habit of consuming soybeans.…”
Section: Sensory Analysismentioning
confidence: 99%
“…[5,6]. Another product that contains PCs and is widely accepted by consumers is cocoa and its derivatives, such as chocolate [1,[7][8][9]. It should be noted that its unique sensory characteristics and functional value are markedly influenced by the composition and concentration of PCs present [10].…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation techniques have been adopted in recent times to improve the retention time of these bioactive in the food, allow for their controlled release, preserve the stability of the bioactive compounds during processing and storage, prevent undesirable interactions with other food matrices, mask unpleasant taste, and increase bioavailability while maintaining the functional properties of the bioactive ingredient and ensuring their efficient absorption in the human digestive system (Ye et al, 2018). A nutritious fruit snack formulation based on dried fig powder and coated with a hydrocolloid solution containing Persian gum and xanthan gum, and chocolate as the outer shell was developed by Yeganehzad et al (2020). The results showed that the hydrocolloid coatings were effective in lowering the hardness and adhesiveness of the coated samples.…”
Section: Development Of Novel Functional Foods: Recent Advancements A...mentioning
confidence: 99%
“…A wide range of edible ingredients could be used as cores and coatings. Nowadays, natural ingredients such as fruits have gained interest as a suitable material for core formulation [5,6].…”
Section: Introductionmentioning
confidence: 99%